The intraday reliability of the reactive strength index calculated from a drop jump in professional men`s basketball - Markwick, W. J.; Bird, S. P.; Tufano, J. J.; Seitz, L. B.; Haff, G. G. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To evaluate the reliability of the Reactive Strength Index (RSI) and jump-height (JH) performance from multiple drop heights in an elite population. Methods: Thirteen professional basketball players (mean ±SD age 25.8 ± 3.5 y, height 1.96 ± 0.07 m, mass 94.8 ± 8.2 kg) completed 3 maximal drop-jump attempts onto a jump mat at 4 randomly assigned box heights and 3 countermovement-jump trials. Results: No statistical difference was observed between 3 trials for both the RSI and JH variable at all the tested drop heights. The RSI for drop-jump heights from 20 cm resulted in a coefficient of variation (CV) = 3.1% and an intraclass correlation (ICC a) = .96, 40 cm resulted in a CV = 3.0% and an ICC a = .95, and 50 cm resulted in a CV = 2.1% and an ICC a = .99. The JH variable at the 40-cm drop-jump height resulted in the highest reliability CV = 2.8% and an ICC a = .98. Conclusion: When assessing the RSI the 20-, 40-, and 50-cm drop heights are recommended with this population. When assessing large groups it appears that only 1 trial is required when assessing the RSI variable from the 20, 40-, and 50-cm drop heights.